2001
DOI: 10.1037/0882-7974.16.4.600
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal change in language production: Effects of aging and dementia on grammatical complexity and propositional content.

Abstract: Mixed modeling was used to examine longitudinal changes in linguistic ability in healthy older adults and older adults with dementia. Language samples, vocabulary scores, and digit span scores were collected annually from healthy older adults and semiannually from older adults with dementia. The language samples were scored for grammatical complexity and propositional content. For the healthy group, age-related declines in grammatical complexity and propositional content were observed. The declines were most r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
189
3
13

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(225 citation statements)
references
References 53 publications
9
189
3
13
Order By: Relevance
“…Perhaps this particular b DIF reflects the tendency of older adults, in general, to use grammatically simple speech (Kemper, Thompson, & Marquis, 2001). Other than this finding, the absence of other meaningful differences within the histrionic PD is consistent with the notion that the criteria for histrionic PD should function similarly for older and younger adults (Agronin & Maletta, 2000).…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…Perhaps this particular b DIF reflects the tendency of older adults, in general, to use grammatically simple speech (Kemper, Thompson, & Marquis, 2001). Other than this finding, the absence of other meaningful differences within the histrionic PD is consistent with the notion that the criteria for histrionic PD should function similarly for older and younger adults (Agronin & Maletta, 2000).…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…Numerous psychological experiments have related idea density to readability (Kintsch, 1998;Kintsch & Keenan, 1973), memory (see, e.g., Thorson & Snyder, 1984), the quality of students' writing (e.g., Takao, Prothero, & Kelly, 2002), aging (Kemper, Marquis, & Thompson, 2001;Kemper & Sumner, 2001), and prediction of Alzheimer's disease. Snowdon et al (1996) found reduced idea density in essays written by individuals who were to develop Alzheimer's disease 50 years later.…”
Section: The Algorithmmentioning
confidence: 99%
“…In this article, we focus on word production, that is, producing the sound or spelling for a word. (For age-related declines in other components of language production, see Kemper, Thompson, & Marquis, 2001.) We review evidence for the decline in word retrieval in old age and describe a cognitive aging model that explains why this language function declines.…”
Section: Introductionmentioning
confidence: 99%